2021
DOI: 10.3892/ol.2021.12890
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‑derived factor inhibits advanced glycation end product‑induced proliferation, VEGF and MMP‑9 expression in breast cancer cells via interaction with laminin receptor

Abstract: Pigment epithelium-derived factor (PEDF) is one of the adipocytokines with multifaceted functions, which may serve a role in the development of various types of cardiometabolic disorders. Advanced glycation end products (AGEs) have been shown to contribute to numerous aging-associated disorders, such as cancer. However, it remains unclear whether and how PEDF exerts antitumor effects in AGE-exposed human breast cancer MCF-7 cells, and therefore this was explored in the present study. NADPH oxidase activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…As mentioned, PEDF has been characterised as an antioxidant. In contrast to our results, it has been shown that PEDF can reduce advanced glycation end product-induced NADPH oxidase-dependent ROS generation in MCF-7 cells [ 41 ], though this was not in relation to Dox. Other studies have also identified PEDF-induced inhibition of NADPH oxidase-dependent ROS generation, including in human umbilical vein endothelial cells and H9c2 cells [ 32 , 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…As mentioned, PEDF has been characterised as an antioxidant. In contrast to our results, it has been shown that PEDF can reduce advanced glycation end product-induced NADPH oxidase-dependent ROS generation in MCF-7 cells [ 41 ], though this was not in relation to Dox. Other studies have also identified PEDF-induced inhibition of NADPH oxidase-dependent ROS generation, including in human umbilical vein endothelial cells and H9c2 cells [ 32 , 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, PEDF suppresses MMP-9 gene expression by MCF-7 cells, and this is reportedly blocked by a neutralizing antibody against the laminin receptor. 34 It is likely that PEDF inhibits MMP-9 expression in various types of cells via distinct receptors. The interdependent interaction of PNPLA2 and LR and the core domain selected by PEDF are largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ROS had been found to induce Rho family GTPase-dependent cytoskeletal rearrangement, accelerate MMP-dependent ECM protein degradation, and promote hypoxia-inducible factor-dependent angiogenesis, thus participating in the EMT process ( 37 , 52 , 53 ). MYOF had been shown to regulate the expression of MMPs and EMT.…”
Section: Discussionmentioning
confidence: 99%